2012
DOI: 10.1038/jhh.2012.10
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum visfatin at 11–13 weeks’ gestation in preeclampsia

Abstract: The objective of this study was to determine if the maternal serum levels of visfatin in the first trimester of pregnancy are altered in cases that develop preeclampsia (PE) and whether the levels are related to placental perfusion reflected in uterine artery pulsatility index (PI). Serum visfatin and uterine artery PI were measured at 11(+0)-13(+6) weeks in 80 cases that developed PE and 240 unaffected controls. The median visfatin and uterine artery PI multiple of the unaffected median (MoM) in the outcome g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
1
9
1
1
Order By: Relevance
“…The pathogenesis of pregnancy-associated hypertensive disorders involves complex immunopathogenic mechanisms and it is highly likely that the observed associations of visfatin in PE might be due to these immunological mechanisms rather than simple metabolic effects. This is also supported by the study by Ferreira et al ( 2013) who report serum visfatin levels at 11-13 weeks to be increased in women who develop PE. These authors suggest that such an increase might be mediated by a mechanism unrelated to impaired placental perfusion.…”
Section: Pre-eclampsiasupporting
confidence: 66%
“…The pathogenesis of pregnancy-associated hypertensive disorders involves complex immunopathogenic mechanisms and it is highly likely that the observed associations of visfatin in PE might be due to these immunological mechanisms rather than simple metabolic effects. This is also supported by the study by Ferreira et al ( 2013) who report serum visfatin levels at 11-13 weeks to be increased in women who develop PE. These authors suggest that such an increase might be mediated by a mechanism unrelated to impaired placental perfusion.…”
Section: Pre-eclampsiasupporting
confidence: 66%
“…4,17,18 In contrast to our findings, Wensheng et al, which reported a decrease in serum Visfatin level in preeclamptic pregnant women compared to control. …”
Section: Discussioncontrasting
confidence: 99%
“…Most studies provide evidence for increased plasma visfatin levels in PE as compared with normotensive pregnant 16,20 or increased serum visfatin levels in PE 17,19 and in the 11-13th weeks of pregnancy in women who developed PE. 18 Conversely, other studies showed decreased serum visfatin levels in PE 21 or decreased visfatin expression in the placental bed in PE as compared with normotensive controls. 22 However, we found no significant differences in plasma visfatin/NAMPT levels when we compared the HP, GH and PE groups.…”
Section: Discussionmentioning
confidence: 93%
“…14 Previous studies reviewed the contribution of visfatin/NAMPT in PE. 15 Most findings provide evidence for increased circulating visfatin levels [16][17][18][19][20] in patients with PE, although decreased serum visfatin levels 21 or visfatin expression have also been reported in PE. 22 Moreover, other studies found no differences in circulating visfatin levels when normal pregnant were compared with patients with PE.…”
Section: Introductionmentioning
confidence: 99%